PREVALENSI DAN FAKTOR YANG MEMPENGARUHI STUNTING PADA BALITA DI BANJARMASIN: PREVALENSI DAN FAKTOR YANG MEMPENGARUHI STUNTING PADA BALITA DI BANJARMASIN - Syahrida Wahyu Utami; Nur Cahyani Ari Lestari; Deananda (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
This study aimed to determine the prevalence and factors influencing stunting among children under five in Banjarmasin City. This quantitative research employed a cross-sectional design with a sample of 150 children under five and their mothers selected through stratified random sampling from five districts in Banjarmasin. Data collection was conducted through anthropometric measurements and questionnaires to assess socioeconomic factors, maternal knowledge, and health practices. Results showed that the stunting prevalence in Banjarmasin was 24.7%, with significant associations between stunting and maternal education (p=0.008), family income (p=0.012), maternal knowledge of nutrition (p=0.015), exclusive breastfeeding (p=0.023), and complementary feeding practices (p=0.007). The study recommends strengthening nutritional education programs, improving access to quality healthcare services, and enhancing economic support for vulnerable families to reduce stunting prevalence in Banjarmasin.